Hypodontia of Upper Lateral Incisors - Late Orthodontic-Prosthetic Therapy - J. Racek; T. Dostálová (Czech Dental Chamber, 2005)
The authors present the procedure and result of the late orthodontic-prosthetic therapy of skeletodental anomaly of the Angle II/1 class with hypodontia of upper lateral incisors. The defect caused disorders in the esthetic features of the face, especially due to variant configuration of the upper frontal part of the teeth. The orthodontic adjustment employed the method of "straight wire" combined with features of other techniques. Retention of the result was secured by prosthetic reconstruction - fixed substitutions from metal-ceramics and a solid retained with a multi-fiber wire in the frontal part of the teeth. This combined orthodontic-prosthetic therapy in a multidisciplinary way resulted in the adjustment of dentoalveolar component, esthetic and functional rehabilitation in the upper tooth arch.